Technical Efficiency Of Private Hospitals In Kamrup (Metro) District, Assam: An Application Of Two Stage Data Envelopment Analysis model (Indian Journal of Public Health Research & Development, 2024)
Healthcare resources should not be misused as such resources can save people's life. Further, avoiding excessive resource employment can help minimize production costs. In this regard, measuring technical efficiency is essential as it helps identify the resource utilization level against the output level. The present study has estimated the relative technical efficiency scores of private hospitals in the Kamrup (Metro) district of Assam. The data for the study is collected from primary and secondary sources for the year 2019. Bootstrapping Data Envelopment Analysisis applied considering two outputs and six input variables.  All the hospitals are technically inefficient; however, small size hospitals have shown better performance in terms of technical efficiency than big size hospitals.The study has not distinguished the number of inpatients based on the resources consumption. In this context, there is a further scope to improve the study. However, this is the first attempt to analyse the performance of private hospitals in terms of technical efficiency in Assam. It will help the management of concerned hospitals to improve their resource utilisation strategy.
Keywords: healthcare resource, technical efficiency, data envelopment analysis, performance.